PROJECT BASED LEARNING APPROACH TO IMPROVE STUDENTS’ ABILITY TO WRITE DESCRIPTIVE TEXT (A Classroom Action Research at Grade X SMAN I Bengkulu Selatan) - Vera Maria Shanti; Syahrial .; Irwan Koto (JOALL (Journal of Applied Linguistics and Literature), 2016)
This study was a classroom action research. It was aimed to explain whether Project Based Learning can improve students’ ability in writing descriptive text and step of Project Based Learning which improved the students’ ability to write descriptive text at grade X of SMAN 1 Bengkulu Selatan in the 2015/2016 academic year. The subjects of this study were 35 students, consisted of 10 females and 25 males. The instruments of this study were writing tests, students’ observation checklists, teacher’s observation checklist, and  interview.  The  study  was  conducted in  two  cycles  which  included  plan, action, observation, and reflection. The evaluation test was administered at the end of each cycle. Based on the result of the study, the improvement of students’ mean score in cycle1 and cycle 2 was significant. It was proven that the students’ mean score in cycle 1 that70.45 increased into 80.31 in cycle 2. To conclude, Project Based Learning was effective to improve students’ ability to write descriptive text and also step 4 of Project BasedLearning approach; monitor the students and the progress of the project became the best step which improved the students’ ability to write descriptive text at grade X SMAN IBengkulu Selatan. To suggest, English teachers can apply Project Based Learning approach as one of the alternative ways to improve students’ writing ability and to improve students’ academic achievement.